Hall effects and rotation effects on MHD flow past an exponentially accelerated vertical plate with combined heat and mass transfer effects - Thamizhsudar, Muthuperumal; Pandurangan, J.; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
A theoretical solution of flow past an exponentially accelerated vertical plate in the presence of Hall current and MHD relative to a rotating fluid with uniform temperature and mass diffusion is presented. The dimensionless equations are solved using the Laplace method. The axial and transverse velocity, temperature and concentration fields are studied for different parameters such as the Hall parameter, Hartmann number, Rotation parameter, Schmidt number, Prandtl number, thermal Grashof number and mass Grashof number.
Keywords: Hall effect; MHD flow; rotation; exponentially; accelerated plate; temperature; mass diffusion